Development of in-house phantoms from polyester resin and methyl ethyl ketone peroxide materials with various diameters:Investigation their CT numbers for various tube voltages and field of views - Luthfi Nurrahma Shofiana; Choirul Anam; Heri Sutanto; Rin Hafsatul Asiah; Riski Nihayati; Ansory Khaerul; Geoff Dougherty (Diponegoro University Semarang Indonesia, 2021)
Development phantoms with various sizes reflecting the variation among patients to investigate the accuracy size-specific dose estimate (SSDE)is essential. The aim of this work was to develop in-house phantoms from polyester resin (PR) and methyl ethyl ketone peroxide (MEKP) for various diameters and investigate the CT numbers of the phantoms with various tube voltages and reconstructed field of views (FOV). In-house phantoms with diameters of 8, 16, 24, and 32 cm were developed. The phantoms were made from the PR and MEKP materials. The composition of MEKP was 0.3 wt% and PR was 99.7%. The phantoms were scanned with a Siemens SOMATOM Emotion 6 CT scanner with various tube voltage (i.e. 80, 110, and 130 kVp), and various field of views (FOVs) (i.e. 35, 40, 45, 50 cm). CT numbersof the phantoms for various diameters, tube voltages and FOVs were investigated. It was found that the CT number was in range of 86 HU to 147 HU. The CT number increased with the increases of diameter and tube voltage. However, the CT number was independent with the FOV. The in-house phantom based on PR andMEKP with various diameters from 8 cm to 32 cm have been successfully developed. The CT numbers of the phantoms depend on diameter and tube voltage,but do not depend with the FOV.